Young mom, short kid: Examining social, biological and health and nutrition service factors linking adolescent pregnancy to early childhood undernutrition in India (P10-011-19) - Nguyen, Phuong Hong; Scott, Samuel P.; Neupane, Sumanta; Tran, Lan Mai; Menon, Purnima (Oxford University Press, 2019)
Adolescent pregnancy is a global public health concern and one in five adolescents live in India, where early marriage is widely practiced. We sought to examine linkages between adolescent pregnancy and child undernutrition using a holistic approach.